Moisture sorption and thermodynamic properties of Camellia oleifera seeds as influenced by oil content - Zhu, Guangfei; Jin, Qi; Liu, Yanhong; Lin, Yawen; Wang, Jun; Li, Xingyi (International Journal of Agricultural and Biological Engineering, 2021)
Moisture sorption isotherms and thermodynamic properties of Camellia oleifera seeds as influenced by oil content were investigated. Moisture desorption and adsorption isotherms of Camellia oleifera seeds, kernels and shells from three varieties were determined using constant temperature and humidity chamber method at different temperatures (10°C, 25°C, and 40°C) with water activity ranging from 0.20 to 0.90. Six selected mathematic models were employed to fit the experimental data. The Peleg model gave the best results for both seeds and kernels and Langmuir model was the best for shells. The difference of equilibrium moisture contents at the same water activities during desorption and adsorption indicated the occurrence of hysteresis of adsorption processes and the equilibrium moisture contents tended to decrease with the increasing oil content and temperature. The binding energy and average capacity per unit mass decreased with increasing temperature and oil content. The relationships between water activity and the logarithm of sorption activity showed the capillary porous body characteristics of the seeds.Keywords: Camellia oleifera seeds, moisture desorption and adsorption isotherms, equilibrium moisture content, oil content, thermodynamic propertyDOI: 10.25165/j.ijabe.20211401.5457Citation: Zhu G F, Jin Q, Liu Y H, Lin Y W, Wang J, Li X Y. Moisture sorption and thermodynamic properties of Camellia oleifera seeds as influenced by oil content. Int J Agric & Biol Eng, 2021; 14(1): 251–258.